Reconstruction of Different Religion Inheritance through Wajibah Testament - Rosadi, Aden; Ropiah, Siti (SCAD Independent, 2020)
The basic principle of the judge in the decision of the Supreme Court No.16K / AG / 2010 was borrowed which according to some heirs of non-Muslim thinkers of Islam inherited inheritance through borrowed roads. Their opinion as stated by Classical Islamic Scholars. The authorities must exclude part of the legacy of the person who died as proof of him even though he did not inherit it beforehand, based on the premise that the authorities must ensure the rights of people who have not been fulfilled. According to the legal system in Indonesia, the body will include being borrowed into the absolute competence of religious courts based on Law No. 7 of 1989 concerning the Religious Courts related to Law No. 3 of 2006 concerning amendments to Law No. 7 1989 concerning the Religious Courts. Judges who refer to the inheritance of Islam in Indonesia are conducted by judges in the religious court environment with the first absolute level of competence as mandated by law.